Ten meditations on government venture capital. Issue 3 (3rd July 2021) - Murray, Gordon
ABSTRACT: This paper reflects on the policy formation process in the burgeoning area of government's involvement in venture capital finance (VC) over the two decades 2000–2020. It looks at both why and how government VC funds (GVC) have evolved. The increasingly common vehicle of "hybrid" co-investment funds, which include both public and private VC investors, is analysed. The evolution of public intervention in VC markets over time is acknowledged while noting that significant operational challenges remain. The rubric of Ten Meditations is employed as a device to communicate both problem and prescription across the academic/policy maker divide.